2008
DOI: 10.1242/dev.016378
|View full text |Cite
|
Sign up to set email alerts
|

Cell-autonomous requirement for β1 integrin in endothelial cell adhesion, migration and survival during angiogenesis in mice

Abstract: β1 integrin (encoded by Itgb1) is established as a regulator of angiogenesis based upon the phenotypes of complete knockouts of β1 heterodimer partners or ligands and upon antibody inhibition studies in mice. Its direct function in endothelial cells (ECs) in vivo has not been determined because Itgb1-/- embryos die before vascular development. Excision of Itgb1 from ECs and a subset of hematopoietic cells, using Tie2-Cre, resulted in abnormal vascular development by embryonic day(e) 8.5 and lethality by e10.5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
121
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(139 citation statements)
references
References 41 publications
9
121
1
Order By: Relevance
“…In line with these results, genetic evidence supports that b1-integrins are essential for in vivo angiogenesis [3,4,41,49,52]. Since silencing of Brag2 enhanced b1-integrin-dependent adhesion and a5b1-integrin surface expression, we investigated the underlying mechanisms affecting b1-integrin function in EC.…”
Section: Brag2 Differentially Regulates B1-and Avb3-integrinssupporting
confidence: 52%
See 2 more Smart Citations
“…In line with these results, genetic evidence supports that b1-integrins are essential for in vivo angiogenesis [3,4,41,49,52]. Since silencing of Brag2 enhanced b1-integrin-dependent adhesion and a5b1-integrin surface expression, we investigated the underlying mechanisms affecting b1-integrin function in EC.…”
Section: Brag2 Differentially Regulates B1-and Avb3-integrinssupporting
confidence: 52%
“…However, additional studies will be required to clarify the underlying molecular mechanisms in EC. Based on the fact that b1-integrins are essential for angiogenesis [4,49,52], we focused in the present study on the effects of Brag2 on b1-integrins in EC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The b1-subunit, which can partner with 12 different a-chains and plays a central role in cell-matrix adhesion, has been also investigated with EC-specific gene targeting approaches in mice. Constitutive targeting of Itgb1, the gene encoding integrin b1, in ECs was found to be incompatible with normal morphogenesis of the embryonic vasculature and survival beyond midgestation [12][13][14] . Although this work has established that endothelial Itgb1 gene function is required for angiogenic sprouting but not for the assembly of the first vessel primordia by vasculogenesis, insight into the precise function of integrin b1 in the regulation of angiogenesis was limited by early embryonic lethality.…”
mentioning
confidence: 99%
“…Genetic deletion of b1 integrin has been particularly informative, perhaps because several endothelial integrin heterodimers (i.e., a1, a2 a3, a4, a5, a6, av heterodimers with b1) are affected by loss of b1 integrin. Several studies showed that b1 loss in endothelial cells results in aberrant endothelial adhesion and migration, and consequent defects in angiogenesis and embryonic lethality (Tanjore et al 2007;Carlson et al 2008). Zovein et al (2010) specifically investigated effects of endothelial b1 loss on apical-basolateral polarity and reported that arteries are selectively affected.…”
Section: Vegf-directed Blood Vessel Patterningmentioning
confidence: 99%